2014
DOI: 10.4244/eijv10i1a12
|View full text |Cite
|
Sign up to set email alerts
|

Validation of residual SYNTAX score with second-generation drug-eluting stents: one-year results from the prospective multicentre SEEDS study

Abstract: Twelve-month TVF was significantly higher in the highest rSS group; rSS with a cut-off of 5 might therefore allow the risk stratification of patients with complex lesions treated with a second-generation drug-eluting stent (Clinical-Trials.gov identifier: NCT 01157455).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
6
22
2
Order By: Relevance
“…With the SYNTAX score proposed as a tool to quantify the complexity of coronary revascularization, the score was used to evaluate optimal treatment duration and predict clinical outcomes after PCI . Because complete coronary revascularization has been shown to improve clinical outcomes, rSS, which is as an index of completeness of coronary revascularization after PCI, provides better prognostic information . Indeed, higher rSS (rSS > 0) was associated with higher rates of TLF, NACE and PoCE within 1 year after stent implantation in this study, which was consistent with the results of previous studies .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With the SYNTAX score proposed as a tool to quantify the complexity of coronary revascularization, the score was used to evaluate optimal treatment duration and predict clinical outcomes after PCI . Because complete coronary revascularization has been shown to improve clinical outcomes, rSS, which is as an index of completeness of coronary revascularization after PCI, provides better prognostic information . Indeed, higher rSS (rSS > 0) was associated with higher rates of TLF, NACE and PoCE within 1 year after stent implantation in this study, which was consistent with the results of previous studies .…”
Section: Discussionsupporting
confidence: 88%
“…As an angiographic tool to quantify the complexity of CAD based on location and the characteristics of lesions, the SYNTAX score (SS) was significant for guiding clinical decisions and predict long‐term outcomes after PCI . Residual SYNTAX score (rSS), which was proposed as an index of completion of revascularization after PCI, showed superior predictive capabilities for ischemic events .…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that inhibition of LPA1 by ki16425 reduced LPS-induced phosphorylation of I-κB, p38 MAPK, and Erk1/2, and cytokine release in mouse lung epithelial cells [11]. To examine if similar physiology may be active in the abdominal LPS model, we evaluated the effect of ki16425 on LPS-induced signaling and cytokine release in the hepatocyte cells HepG2 and macrophage cell line Raw264, as cell death or inflammatory responses of these cells contribute to the pathogenesis of liver failure (2426). LPS-induced phosphorylation of PKCδ and p38 MAPK were attenuated by ki16425 in HepG2 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SEEDS trial (NCT 01157455) design has previously been described in detail . Briefly, the SEEDS trial was a prospective, multicenter, open‐label registry trial in which 1,900 patients were enrolled in 48 sites in Asia (mainly China) from June 2010 to December 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The SYNTAX revascularization index (SRI) quantifies the percentage of revascularized myocardium and has been shown to be predictive of adverse ischemic events after PCI with first‐generation drug‐eluting stents (DES) ; however, to the best of our knowledge, whether this association exists in a population of patients with complex CAD undergoing contemporary PCI with second‐generation DES has never been shown. Therefore, as part of A Registry to Evaluate Safety and Effectiveness of Everolimus Drug Eluting Stent for Coronary Revascularization (SEEDS) , we aim to evaluate the impact of the completeness of revascularization, expressed by the SRI, on 2‐year adverse ischemic events in a population of patients with complex CAD undergoing PCI with second‐generation everolimus‐eluting stents .…”
Section: Introductionmentioning
confidence: 99%